A dual PI3K α/mTOR inhibitor cooperates with blockade of EGFR in PTEN-mutant glioma - Fan, Qi-Wen (2007)
We have shown previously that blockade of EGFR cooperates with a pan-selective inhibitor of PI3K in EGFR-driven glioma. In this communication, we tested EGFR-driven glioma differing in PTEN-status, treating with the EGFR inhibitor erlotinib and a novel dual inhibitor of PI3Kα and mTOR (PI-103). Erlotinib blocked proliferation only in PTEN(wt) cells, without further impact by PI-103. Although erlotinib monotherapy showed little effect in PTEN(mt) glioma, PI-103 greatly augmented the antiproliferative efficacy of erlotinib in this setting. To address the importance of PI3K-blockade, we showed in PTEN(mt) glioma that combining PI-103 and erlotinib was superior to either monotherapy, or to therapy combining erlotinib with either rapamycin (an inhibitor of mTOR) or PIK-90 (an inhibitor of PI3Kα). These experiments demonstrate that a dual inhibitor of PI3Kα and mTOR augments the activity of EGFR-blockade, offering a mechanistic rationale for targeting EGFR, PI3Kα, and mTOR in the treatment of EGFR-driven, PTEN-mutant glioma.